Psychophysiogical aspects of shalat: A chronobiology measurement - Annatagia, Libbie; Trimulyaningsih, Nita; Sari, Endah Puspita (Asosiasi Psikologi Islam (API) Himpsi, 2017)
Shalat is an obligation for Moslems. It is written in Al Qur’an and Hadith. This study examined the psychophysiological aspects of those who perform obligatory shalat. The subject of this study was a 22 years old male student. The data was obtained from chronobiology devices named Stress Pilot and Smardwatch. Subject was measured by stress pilot two times: 2 hours after shalat and 20 minutes after shalat. Subject also measured by Smardwatch within 24 hours. Furthermore, the data from smardwatch were transfered to the computer. This study found that subject had a good stress regulation (quality of regulation was in level 31: concentration-relaxation, RSA: 34 & 35, age comparison: 61% - 70% and 71% - 80%). These findings prove that shalat give a good pychophysiological effect for subject.